Técnicas y lenguajes documentales por el brasileño Eduardo Coutinho - Renó, Denis Porto [UNESP]; Campalans, Carolina; Renó, Luciana Tarlá Lorenzi [UNESP] (Forum XXI, 2015)
1. Introduction. Eduardo Coutinho represents the development and innovation of the Brazilian documentary. His career is still marked by a novel technique of interviews with participants also mix documentary with other communication techniques, especially fiction and journalism. This article provides a recovery path Coutinho and his major works. 2. Method. A literature review and analysis of filmic discourse is applied to understand the history and languages ​​adopted by Coutinho during his career as a documentary. 3. Who was. Before acting as a documentary, Coutinho has studied law but always acted in theater and visual arts. This discussion presents Coutinho before documentaries. 4. Frames by Eduardo Coutinho. The main works of the documentary are presented, as well as its important features that transform the filmography of director in one of the most important in Brazil. 5. Conclusions. We conclude that Eduardo Coutinho has left a gap in the Brazilian documentary, since his death in 2014. However, their contributions are transformed the genre, as the results presented in the article.

1. Introducción. Eduardo Coutinho representa el desarrollo y la innovación del documental brasileño. Todavía, su trayectoria es marcada por una técnica novedosa de entrevistas con los participantes, además de la mezcla del documental con otras técnicas comunicacionales, especialmente la ficción y el periodismo. Este artículo ofrece una recuperación de la trayectoria de Coutinho y de sus principales obras. 2. Método. Se aplica una investigación bibliográfica y una análisis de discurso fílmico para comprender la trayectoria y los lenguajes adoptados por Coutinho durante su carrera como documentalista. 3. Quien fue. Antes de actuar como documentalista, Coutinho ha estudiado Derecho pero siempre actuó con teatro y artes visuales. Esa discusión presenta Coutinho antes de los documentales. 4. Encuadres de Eduardo Coutinho. Las principales obras del documentalista son presentadas, así como sus características importantes que transforman la filmografía del director en una de las más importantes de Brasil. 5. Conclusiones. Se concluye que Eduardo Coutinho ha dejado un hueco en el documental brasileño, desde su muerte en 2014. Sin embargo, sus contribuciones son transformaron el género, como presentado en los resultados del artículo.
Technical and documentary languages by Brazilian Eduardo Coutinho
Keywords: Communication; Audiovisual narratives; Documentary; Language; Comunicación; Narrativas audiovisuales; Documental; Lenguaje